The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1634/theoncologist.12-4-465
|View full text |Cite
|
Sign up to set email alerts
|

Design of Clinical Trials of Radiation Combined with Antiangiogenic Therapy

Abstract: LEARNING OBJECTIVESAfter completing this course, the reader will be able to:1. Discuss the impact of tumor angiogenesis and hypoxia on the outcome of radiation therapy.2. List the classes of antiangiogenic agents that are in clinical development.3. Identify mechanisms by which antiangiogenic therapy can enhance radiation efficacy.Access and take the CME test online and receive 1 AMA PRA Category 1 Credit ™ at CME.TheOncologist.com CME CME ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 106 publications
1
50
0
3
Order By: Relevance
“…19,20 The effect of combining radiation and vandetanib on normal tissue is currently unknown, however it has been shown in both preclinical and clinical trials that use of VEGF inhibitors with radiation may result in higher rates of normal tissue toxicity such as induction of thrombosis, hemorrhage, and bowel toxicities. [21][22][23] In contrast, it was postulated that combination of radiotherapy with inhibitors of angiogenesis may actually decrease these risks because radiotherapy has been used to prevent hemorrhage. 24 Overall, the investigation of agents such as vandetanib in combination with radiation in normal tissue is lacking, and thus will be a major focus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The effect of combining radiation and vandetanib on normal tissue is currently unknown, however it has been shown in both preclinical and clinical trials that use of VEGF inhibitors with radiation may result in higher rates of normal tissue toxicity such as induction of thrombosis, hemorrhage, and bowel toxicities. [21][22][23] In contrast, it was postulated that combination of radiotherapy with inhibitors of angiogenesis may actually decrease these risks because radiotherapy has been used to prevent hemorrhage. 24 Overall, the investigation of agents such as vandetanib in combination with radiation in normal tissue is lacking, and thus will be a major focus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…That hypothesis also accords with results of a study by Kulik et al 50 , which prospectively evaluated patients receiving 90 Y with and without sorafenib, and which also pointed toward a sorafenib dose reduction (400 mg daily), because dose reductions were required for all patients in the combined treatment arm. creating a vasculature normalization window 38 . Since the introduction of angiogenic agents such as sorafenib for advanced hcc, there has been a theory that such agents could potentially "normalize" the tumour vasculature 54 , which is typically more disorganized.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour vasculature is tortuous and leaky 38,39 , and although it can deliver oxygen and nutrients to the core of the tumour, it is thought to be inefficient compared with normal vessels. Antiangiogenic agents have been shown to normalize the vessels and allow them to deliver oxygen more efficiently to the core of hcc tumours 40,41 , which in fact has been associated with enhanced radiation-induced tumour regression because sensitivity to radiation is increased 38 . The synergy between intra-arterial radioembolization and sorafenib therapy has also been investigated in an in vitro study, which showed an advantage of combining the two treatment modalities in human and murine hepatoma cell lines 42 .…”
Section: Rationale For Combining Sorafenib and 90 Y Therapymentioning
confidence: 99%
“…Anti-angiogenic cancer therapy that targets tumor-induced angiogenesis by affecting endothelial cells has yielded promising outcomes in clinical trials [43]. Angiogenesis is comprised of multiple tightly controlled, complex processes and is triggered by an interaction with pro-angiogenic factors, especially VEGF, and its receptors [37].…”
Section: Discussionmentioning
confidence: 99%